Poly(ADP‐ribose)polymerase inhibitors‐associated myeloid neoplasms: a retrospective study from the French Network of Pharmacovigilance centres - Morice, Pierre‐Marie; Genthon, Alexis; Boyer, Thomas; Bihan, Kévin; Mahé, Julien; Sourisseau, Anthony; Peyrouzet, Hélène; Miremont, Ghada; Lepelley, Marion; Stefani, Laëtitia; Gaboriau, Louise; Rocher, Fanny; et al. (British Journal of Haematology, 2021)
The British Journal of Haematology publishes original research papers in clinical, laboratory and experimental haematology. The Journal also features annotations, reviews, short reports, images in haematology and Letters to the Editor.